(untitled) (Bangladesh Agronomy Journal, 2020)
The experiment was conducted at Jute Agriculture Experimental Station (JAES), Manikganj and Jute Research Regional Station, Faridpur during 2019 to find out the effect of weeding and herbicide management on fibre yield and yield attributes of Tossa jute (Var. O-9897) cultivation. Two herbicide treatments, such as; W1 = Fenoxaprop-p-ethyl (Whip Super 9 EC) and W2 = Ethoxysulfuron (Sunrice ® 150WG) were tested. There were 14 treatments. T1- T6 treatments did not include hand weeding which was done 20 days after the herbicide spray [T1 = 100% recommended doses (RD) of both W1and W2 where W2 was sprayed one day after that of W1, T 2 = 50% dose both of W1and W2 where W2 was sprayed one day after that of W1, T3 = 100% dose of both W1 and W2 where both of the herbicide mixed together and sprayed on the same day, T4 = 50% dose of both W1 and W2 where mixture of both were sprayed on the same day, T5 = only 100% dose of W1, T6 = only 100% dose of W2]. The treatments T7 - T12 included one had weeding following the application of herbicides [T7 = 100% dose both of W1 and W2 where W2 was sprayed 1 day after that of W1, T8 = 50% dose both of W1 and W2 where W2 was sprayed 1 day after of W1, T9 = 100% dose both of W1 and W2 were mixed and sprayed together on the same day, T10 = 50% dose both of W1 and W2 mixed together and sprayed same day, T11 = only 100% dose of W1, T12 = only 100% dose of W2]. The treatments T13 and T14 did not include herbicide application [T13 = Two hand weeding (20-25 and 45-50 DAS) and T14 = control with no herbicide application]. The experiment was laid out in RCBD with three replications. Results revealed that Khudesama (Echinochloa colonum) and Angulighash (Digitaria sanguinalis), Khudesama and Mutha (Cyperus rotundus) were best controlled by herbicide application. T3 gave highest fibre yield of 1.89 tha-1 when W1 and W2 sprayed at the same day with 100% RD. In case of one weeding 20 days after spray fibre yield and stick yield were differed significantly as compared to those of control at Manikganj. Treatment T7 gave highest fibre yield (3.11 t ha-1) when W2 sprayed after 1 day of W1 with 100% RD. At Faridpur, T3 gave the highest fibre yield (2.68 t ha-1) when W1 and W2 sprayed at the same day with 100% RD. Incase of one weeding 20 days after spray, T7 gave highest fiber yield (2.79 t ha-1) when W2 was sprayed 1 day after that of W1 with 100% RD. Bangladesh Agron. J. 2020, 23(1): 101-106